2010
DOI: 10.1002/humu.21422
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation within the fork-head domain of the forkhead box G1 Gene (FOXG1) affects its nuclear localization

Abstract: ABSTRACT:The forkhead box G1 (FOXG1) gene has recently been associated with the congenital variant of Rett syndrome, and so far 17 mutations have been reported. We screened the coding region in 150 patients affected by postnatal microcephaly, and identified two mutations: the c.326C>T (p.P109L) substitution inherited from the healthy father; and the de novo c.730C>T transition, which induces the p.R244C mutation within the DNA-binding forkhead domain. This latter mutation is carried by an 8-year-old girl, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
5
19
0
1
Order By: Relevance
“…Our male patient carries a de novo p.Ala193Thr missense mutation. To date, only 3 missense mutations in FOXG1 have been reported [Mencarelli et al, 2010;Le Guen, 2011b]. Interestingly, all 4 missense mutations, including the one identified in our patient, are located within the highly conserved DNA-binding forkhead domain of the protein (amino acids 181-275).…”
Section: Discussionmentioning
confidence: 88%
“…Our male patient carries a de novo p.Ala193Thr missense mutation. To date, only 3 missense mutations in FOXG1 have been reported [Mencarelli et al, 2010;Le Guen, 2011b]. Interestingly, all 4 missense mutations, including the one identified in our patient, are located within the highly conserved DNA-binding forkhead domain of the protein (amino acids 181-275).…”
Section: Discussionmentioning
confidence: 88%
“…Including this study, 26 point mutations, 25 CNVs, and 2 t(2;14) balanced translocations have been reported in patients with a FOXG1-related phenotype. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][17][18][19][20][21][22] The male-to-female ratios is 7/26 (27%) for point mutations and 13/25 (52%) for CNVs. The preponderance of females in patients positive for a FOXG1 point mutation is most probably due to the initial description of FOXG1 deleterious alleles in females with congenital RTTs.…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations in the Forkhead box G1 (FOXG1) gene, encoding a brain-specific transcriptional repressor essential for the development of the telencephalon, were found to be responsible for congenital [1][2][3][4][5][6][7] or classical 2,5 Rett syndrome (RTT) in females and also in males. [5][6][7] Copy number variations (CNV) in 14q12 containing the FOXG1 gene have been identified in both genders in patients suffering from neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…17 Philippe et al, 25 Le Guen et al, 24,35 Mencarelli et al, 15 Bahi-Buisson et al, 16 Takahashi et al 26 …”
Section: Chromosomal Microarray Analysis Methodsunclassified